Construction and Optimization of the de novo Biosynthesis Pathway of Mogrol in Saccharomyces Cerevisiae - Wang, Siyu; Xu, Xianhao; Lv, Xueqin; Liu, Yanfeng; Li, Jianghua; Du, Guocheng; Liu, Long (Frontiers in Bioengineering and Biotechnology, 2022)
Mogrol plays important roles in antihyperglycemic and antilipidemic through activating the AMP-activated protein kinase pathway. Although the synthesis pathway of mogrol in Siraitia grosvenorii has been clarified, few studies have focused on improving mogrol production. This study employed a modular engineerin g strategy to improve mogrol production in a yeast chassis cell. First, a de novo synthesis pathway of mogrol in Saccharomyces cerevisiae was constructed. Then, the metabolic flux of each synthetic module in mogrol metabolism was systematically optimized, including the enhancement of the precursor supply, inhibition of the sterol synthesis pathway using the Clustered Regularly Interspaced Short Palindromic Repeats Interference system (CRISPRi), and optimization of the expression and reduction system of P450 enzymes. Finally, the mogrol titer was increased to 9.1 μg/L, which was 455-fold higher than that of the original strain. The yeast strains engineered in this work can serve as the basis for creating an alternative way for mogrol production in place of extraction from S. grosvenorii.